3D-CFD flow driven performance analysis of new non-cylindrical helical vertical axis wind turbine for fluctuating urban wind conditions. Issue 1 (31st March 2022) - Basker, Indhumathy; Nainangkuppam Venkatesan, Mahalakshmi
ABSTRACT: Wind gusts are the serious parameters that need to be considered for the aerodynamic study of any wind turbine. This article investigates the performance of a new vertical axis wind turbine with non-cylindrical helical turbine blades for an unsteady gusty wind prevailing in urban and suburban environments. In this work, three-dimensional CFD analysis with dynamic mesh has been carried out for two gust velocities of 0.6 m/s and 2 m/s with a mean free stream velocity of 4 m/s. The behavior of the proposed helical turbine during start-up and steady operation was analyzed. The results show that the gust introduced during the start-up period aids in torque production, enabling it to reach the steady-state faster. The turbine reached the steady-state 54.71% earlier under gusty wind than under constant wind. However, on the scale of Cp, the turbine performed well under constant wind during the start-up period. The gust injection during the steady-state period showed a 1.97% increase in Cp of the turbine than under constant wind velocity.